MANAJEMEN REKRUTMEN DAN SELEKSI GURU DALAM MENINGKATKAN MUTU PENDIDIKAN PADA LEMBAGA PENDIDIKAN ISLAM: STUDI LITERATURE REVIEW - Nadia Putri Kamila; Sabila Qurrota A'yun; Bambang Sri Anggoro; Sovia Mas Ayu (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of teacher recruitment and selection in improving the quality of education in Islamic educational institutions. The research employed a qualitative approach using a literature review method by examining various scientific journals, books, proceedings, and academic documents relevant to the research topic. Data sources were obtained through Google Scholar, Garuda, DOAJ, and Scopus databases using keywords related to recruitment management, teacher selection, teacher professionalism, and the quality of Islamic education. The data were analyzed using content analysis techniques to identify concepts, strategies, implementation processes, challenges, and the contribution of recruitment and selection management to improving educational quality. The results of the study indicate that teacher recruitment and selection management plays a significant role in obtaining professional, competent, qualified, and Islamic-character educators. The implementation of systematic, transparent, objective, and competency-based recruitment and selection processes can improve learning quality, student achievement, teacher performance, institutional competitiveness, and public trust in Islamic educational institutions. In addition, effective recruitment management supports the creation of a conducive educational environment and sustainable institutional development.